Development of a Scientific Methodological Approach to Expansion of Product Range for Treatment of Infected Wounds - Brkich, Liliana Lyubanovna (Asian Journal of Pharmaceutics (AJP), 2018)
Background: One of the most prominent problems of surgery and dermatology is the rational treatment of pyoinflammatory diseases of skin and post-operative pyogenic complications. Objective: The aim of the study was to develop a scientific methodological approach to expansion of product range for treatment of infected wounds. Materials and Methods: Development of methodology for unbiased assessment of prospects of development of novel drug products for the treatment of infected wounds was performed using information analysis methods. Results: A systemic analysis of active pharmaceutical ingredients used in drug products for wound treatment depending on the wound healing phase allowed to discover the most widely used drug products. A comparative assessment of dosage forms used in infected wounds treatment showed that local wound healing medications were represented primarily by gels or hydrophilic/hydrophobic ointments.Conclusion: Taking obtained results into account, it is shown that the novel drug product for the treatment of infected wounds should be represented by a hydrophilic multicomponent composition, which includes immobilized proteolytic enzymes and polysaccharide complex of chitosan and alkylamidopropyldimethylbenzylammonium.